2020
DOI: 10.1016/j.stemcr.2020.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Human Cerebrospinal Fluid Promotes Neuronal Circuit Maturation of Human Induced Pluripotent Stem Cell-Derived 3D Neural Aggregates

Abstract: Summary Human induced pluripotent stem cell (hiPSC)-derived in vitro neural and organoid models resemble fetal, rather than adult brain properties, indicating that currently applied cultivation media and supplements are insufficient to achieve neural maturation beyond the fetal stage. In vivo , cerebrospinal fluid molecules are regulating the transition of the immature fetal human brain into a mature adult brain. By culturing hiPSC-3D neural aggregates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“… 23,206,207 With this in mind, Izsak et al found that substituting adult human cerebral spinal fluid (hCSF) for common differentiation media in a 3D model of human iPSC derived neural aggregates resulted in rapid gliogenesis, neurogenesis, synapse formation, and neurite outgrowth, with the formation of mature and synchronously active neural networks, as seen in native brain tissue. 208 Limited accessibility aside, with the aim of constructing a controlled and replicable in vitro tissue model, the undefined components of an individual's CSF are not desirable. However, for the formation of patient-specific and translatable cell models for in vitro analysis and/or therapeutic applications, it could be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“… 23,206,207 With this in mind, Izsak et al found that substituting adult human cerebral spinal fluid (hCSF) for common differentiation media in a 3D model of human iPSC derived neural aggregates resulted in rapid gliogenesis, neurogenesis, synapse formation, and neurite outgrowth, with the formation of mature and synchronously active neural networks, as seen in native brain tissue. 208 Limited accessibility aside, with the aim of constructing a controlled and replicable in vitro tissue model, the undefined components of an individual's CSF are not desirable. However, for the formation of patient-specific and translatable cell models for in vitro analysis and/or therapeutic applications, it could be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…The TGF-β1 impact on human neural cells has not yet been reported, therefore we evaluated whether TGF-β1 treatment affects electrophysiological function of human neurons. Since human iPSC-derived neurons are more functional in an 3D neural environment (see Izsak et al, 2019Izsak et al, , 2020, we prepared hiPSC-3D-NA cultures in the absence or presence of 20 ng/ml TGF-β1. We performed cell-attached and whole cell recordings in cells localized at the edges of 3D-NAs, where MAP2AB + neurons are present (Figure 5A).…”
Section: Tgf-β1 Does Not Alter Electrophysiological Function Of Human Ipsc-derived Neuronsmentioning
confidence: 99%
“…During fetal brain development, CSF factors might be crucial to promote differentiation of NSCs into neurons, while in the adult brain, CSF factors rather promote proliferation of ventricular NSCs (Silva-Vargas et al, 2016). Interestingly, human iPSC-NSCs differentiate into neurons and astrocytes when exposed to adult CSF samples (Izsak et al, 2020).…”
Section: The Role Of Choroid Plexus and Csf Factors In Regulating Neural Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This work produced the hypothesis that neuronal circuits play a role in the maturation of the intrinsic properties of thalamic neurons, because it was found that fusion of thalamic organoids with cortical organoids increased the frequency of electrophysiologically mature neurons in the thalamic tissue (Xiang et al, 2019). Furthermore, other studies found that neurons in organoids show spontaneous network formation producing periodic and regular oscillatory events dependent on glutamatergic and GABAergic signaling, reaffirming that neurons in organoids develop axons, synapses, and mature functional properties (Birey et al, 2017;Izsak et al, 2020;Trujillo et al, 2019;Xiang et al, 2017Xiang et al, , 2019. A recent study has pushed the boundaries of using organoids to model neural circuit formation even further by making cortico-motor assembloids that comprised of three organoids fused together (cortical-spinalmuscle).…”
Section: Neural Circuit Formationmentioning
confidence: 71%